Equivalent energy level hybridization approach for high-performance metamaterials design. (15th August 2017) - Liu, Chuanbao; Bai, Yang; Jing, Liqiao; Yang, Yihao; Chen, Hongsheng; Zhou, Ji; Zhao, Qian; Qiao, Lijie
Abstract: Metamaterials have microscopic physical properties highly analogous to real materials, since their characteristic frequencies behave as equivalent energy levels, providing an efficient route to deal with stacked meta-atoms with strong interactions. Based on the hybridization of equivalent energy levels theory, in this paper, we designed transmissive multilayer metasurfaces to convert the handedness of a circularly polarized wave with high efficiency in a broad bandwidth. In stacked metasurfaces, the equivalent energy levels gradually split with an increasing layer number (i.e. meta-atoms). Their hybridization introduces trapped modes with near-unity transmission, contributes to a near-π transmission phase difference and promotes the split modes overlapping to form a broad bandwidth. Through theoretical calculations, numerical simulations and experimental measurements, a four-layer metasurface was shown to exhibit a high transmission conversion coefficient (80–98%) of a circularly polarized wave covering the whole X-band. Furthermore, a multifunctional meta-lens with broad bandwidth was designed and fabricated based on the Pancharatnam-Berry phase to converge or diverge incident Gaussian beams with different handedness at a high efficiency rate. Graphical abstract: Image